Pengaruh Latihan Lari Zig-Zag terhadap Penguasaan Teknik Dasar Dribbling pada Permainan Sepakbola Ekstrakurikuler SDN Sungapan Kecamatan Kadudampit 2018 - Razbie, Ricki Yana; Nurudin, Ahmad Alwi; Soleh, Moch. (utile: Jurnal Kependidikan, 2018)
With the aim of this study is to find out the influence of zigzag runningtraining on mastering the basic dribbling techniques in the football game of SungapanSubdistrict Kadudampit District. as long as the ball is not enough to just kick it but itrequires a variety of basic technical skills, especially basic dribbling techniques thatmust be improved so that all skills become even better in doing agile dribbling masterywith good foot coordination.Experimental research method is a procedure ofexperimental activities with the aim to investigate a problem what is the cause andeffect relationship and how much relationship is there by giving certain treatments toseveral groups, the methodology used is the experiment and the instrument in this studyusing dribbling test, with the number of research samples as many as 15 boysextracurricular football SDN Sungapan.The results showed that the average scoreobtained during the initial test was 18.88 with standard deviation of 1.25. While thefinal test results show an average value of 17.08 with a standard deviation of 1.79. andthe gain score shows an average value of 5.26 with a standard deviation of 0.27. it canbe concluded that there is an increase in the initial and final tests.